Hubungan Kualitas Pelayanan Keperawatan dengan Kepuasan Pasien di RSUD M.M Dunda Limboto - abidju, febri; Ishak, Fifi; Asnawati, Rini (Lembaga Pengembangan Kinerja Dosen, 2026)
Patient satisfaction has become an important indicator in assessing the quality of healthcare services, especially in the era of digitalization and information transparency, while good healthcare services provide effective, safe, and high-quality care supported by adequate resources. This study aimed to determine the relationship between the quality of nursing services and patient satisfaction. The research design used was quantitative. The population consisted of 302 patients, with a sample of 75 patients selected using the Slovin formula. Data analysis was conducted using the chi-square test. The results showed that the highest category of nursing service quality dimensions was classified as good, including reliability with 69 respondents, responsiveness with 68 respondents, assurance with 67 respondents, empathy with 68 respondents, and tangible evidence with 69 respondents. The statistical analysis showed a P-value of 0.033 for reliability, 0.010 for responsiveness, 0.022 for assurance, 0.001 for empathy, and 0.003 for tangible evidence toward patient satisfaction. The study concluded that there was a significant relationship between nursing service quality in terms of reliability, responsiveness, assurance, empathy, and tangible evidence and patient satisfaction at RSUD M.M Dunda Limboto. Hospitals and nurses are expected to continuously improve service quality in order to increase patient trust and satisfaction.